HERMES: Hadamard Encoding and Reconstruction of MEGA-Edited Spectroscopy - Chan, Kimberly L. (Magn Reson Med, 2016)
PURPOSE: To investigate a novel Hadamard-encoded spectral editing scheme and evaluate its performance in simultaneously quantifying N-acetyl aspartate (NAA) and N-acetyl aspartyl glutamate (NAAG) at 3 Tesla. METHODS: Editing pulses applied according to a Hadamard encoding scheme allow the simultaneous acquisition of multiple metabolites. The method, called HERMES (Hadamard Encoding and Reconstruction of MEGA-Edited Spectroscopy), was optimized to detect NAA and NAAG simultaneously using density-matrix simulations and validated in phantoms at 3T. In vivo data were acquired in the centrum semiovale of 12 normal subjects. The NAA:NAAG concentration ratio was determined by modeling in vivo data using simulated basis functions. Simulations were also performed for potentially coedited molecules with signals within the detected NAA/NAAG region. RESULTS: Simulations and phantom experiments show excellent segregation of NAA and NAAG signals into the intended spectra, with minimal crosstalk. Multiplet patterns show good agreement between simulations and phantom and in vivo data. In vivo measurements show that the relative peak intensities of the NAA and NAAG spectra are consistent with a NAA:NAAG concentration ratio of 4.22:1 in good agreement with literature. Simulations indicate some coediting of aspartate and glutathione near the detected region (editing efficiency: 4.5% and 78.2%, respectively, for the NAAG reconstruction and 5.1% and 19.5%, respectively, for the NAA reconstruction). CONCLUSION: The simultaneous and separable detection of two otherwise overlapping metabolites using HERMES is possible at 3T.